Strategi Pengembangan Bahasa Anak Usia Dini Menurut Vygotsky - Arsy; Handayani, Fitri Febri (Jurnal I TIBAR, 2024)
This research discusses strategies for early childhood language development according to Vygotsky. The aim of this research is to determine language development according to Vygotsky at Pertiwi Indralaya Kindergarten and the implications of learning strategies on children's language development. The research subjects were 20 children in Class A of Pertiwi Indralaya Kindergarten. The research results explained that 2 children experienced speech delays. Based on this, there is a strategy to improve children's language in the form of introducing new words by arranging letters and also recognizing words by simulating pictures.